Rebel Rising : a memoir - Wilson, Rebel (New York Simon & Schuster, 2024)
"For decades, Rebel Wilson had single-mindedly focused on her career, making a name for herself through her iconic roles in Pitch Perfect, Bridesmaids, and Isn't It Romantic. Now, she's ready to chronicle the emotional and physical lessons she learned, as well as her most embarrassing experiences. A malaria-induced hallucination? An all-style martial arts fighting tournament? Junior handling at dog shows? And this was all BEFORE she moved to Hollywood! Rebel Rising follows Rebel Wilson's incredible journey of "making it," constantly questioning, "Am I good enough? Will I ever find love? Will I ever change and become healthy?" Rebel writes for the first time about the most personal and important moments in her life--from fertility issues, weight gain and loss, sexuality, overcoming shyness, rejections, and, well... okay there's at least one story thrown in about Brad Pitt! It's all here. This memoir shows us how to love ourselves while making us laugh uncontrollably"--
The drive -- The fertility doctor -- Young Rebel -- Petcetera etc. -- Sweet tooth -- Blue Bay -- Drama -- 42nd Street -- Popular -- New Year's resolutions -- Sweet sixteen -- Head girl -- South Africa -- Malaria -- Becoming a fighter -- Rejection -- Getting fat -- Women aren't funny -- Bridesmaids -- Pitch Perfect -- Sudden international fame -- Letter to my father -- Sacha Baron Cohen and other assholes -- Letter to myself, 2015 -- Late bloomer -- In Atlanta, I'm a 10 -- The year of fun/the year of love -- The tennis player -- Letter to my body, 2020 -- The year of health -- Rebel 4.0 -- My Disney princess -- Roycie.
113573
Keywords: Wilson, Rebel; Motion picture actors and actresses -- Australia -- Biography; Autobiographies (literary works); LGBTQ+ autobiographies; Biographies; Informational works; Documents d'information.